An Investigation into Numerical Uncertainty of 17.500 DWT Model Tanker Resistance - Pria Utama, I Ketut Aria; Purnamasari, Dian; Suastika, I Ketut (Journal of Advanced Research in Applied Mechanics, 2020)
The credibility of computational simulations is related to the quantifying the error. The convergence study is a reduction of the numerical errors associated with simulation parameters. The numerical simulation of 17.500 DWT tanker resistance in calm water conditions at Fr= 0.13 - 0.20 has been investigated by ITTC standard. Two different turbulence models EASM and k-? SST were implemented and deviations in the numerical results are highlighted. The verification is performed by assessing grid quantity and Richardson extrapolations, and uncertainty analysis with the factor of safety methods. The numerical results of total resistance coefficient of two turbulence model were compared with the experimental data. These numerical investigation shows well captured free surface, the wave elevation around the hull are in qualitative agreement with the experimental.